(untitled) (Journal of Asian Development Studies, 2025)
Food insecurity poses a serious and ongoing threat to many developing countries, where rapid population growth has reshaped the landscape of food production and distribution. This study examines the non-linear analysis of urban and rural populations on food security. Besides these effects, it also explores the key determinants of food security, with a special focus on the role of trade openness, foreign direct investment, education, and institutional quality dynamics. The empirical results are estimated using the Panel Quantile Regression approach of 47 developing countries from 2002 to 2023. This approach reveals an inverted U-shaped relationship between both urban and rural populations on food security. The linearized marginal effect shows that the urban population is more vulnerable to food security compared to the rural population in developing countries. Moreover, education enhances food security, while foreign direct investment and trade openness cause food insecurity in developing countries. This study recommends that developing countries should promote sustainable urban development and strengthen rural agriculture systems.